Analisis Teknik Bermain dan Melodi Lagu “Tristezas de um Violão” (Choro Triste No. 1) karya Garoto - Kallu, Juan Kevin; Kadir, Tulus Handra (EDUMUSIKA, 2024)
This study analyzes the guitar techniques and melody in Garoto's *"Tristezas de um Violão"* (Choro Triste No. 1), arranged by Paulo Bellinati. The focus is on identifying classical guitar techniques such as barre, arpeggio, and glissando, and exploring the uniqueness of the melody. Using a descriptive approach and literature study method, data were collected through observation, documentation, and processing of primary and secondary sources. The results reveal that Garoto applied innovative and expressive guitar techniques, emphasizing technical and aesthetic elements that enhance the choro genre. Techniques like smooth glissando and dynamic arpeggios reflect a distinct and emotional playing style. Additionally, the melody structure demonstrates Garoto's creativity in blending traditional and modern elements. In conclusion, this study provides a deep understanding of Garoto's playing style, its relevance to classical guitarists, and its contribution to the choro music genre. The interpretation of the techniques and melodies offers valuable insights for music enthusiasts and inspiration for further development of guitar techniques.